Relasi Harkat Kemanusiaan Sastra Lisan Asal Nama Desa Pintu Jenangan Ponorogo - Suci Ayu Latifah; Ik Sekar Rachmawati; Abu Yazid (Lingua Susastra, 2022)
Oral literature has now penetrated into written literature to extend the life of intangible cultural heritage. In the case of oral literature, the name of Pintu Village has been written into the Babad Ponorogo book. Pintu Village is one of the 17 villages in Jenangan District, Ponorogo. The village has a story so the name is taken from that story as well. Therefore, this study aims to describe the human relations of oral literature in Pintu Jenangan Ponorogo Village. Until now, oral literature originating from Pintu Village has a strong existence. For this reason, in this study, researchers will explore the relationship between the human dignity of the Pintu Village oral literature, as well as its function for human life. The relationship of human dignity focuses on the four human relationships, namely humans with God (his creatures), humans with fellow humans, humans with themselves, and humans with nature. Interviews and observations were carried out as a form of extracting data related to the object of research. Furthermore, the analysis uses two theories, namely the interactive analysis of Kluckholn and Strodtbeck and the structural functional analysis of Talcott Parsons. The two theories will lead to the four human relations and the function of literary works as a social system. The results of data mining show that there are four human relations in the oral literature of Pintu Jenangan Ponorogo Village.